ショウワ キチ ニオケル エートケン リュウシ ノウド ニツイテ ジョホウ ダイ1カイ ナンキョク キスイケン シンポジウム - 岩井, 邦中; イワイ, クニモト; IWAI, Kunimoto (1979)
P(論文) 昭和基地において1977年2月から1978年1月まで1年間,ポラック型のエアロソル自動測定装置によってエートケソ粒子高度の測定を行った.エアロソル濃度は冬期に低く,夏期に高い年変化があった.その濃度は冬期に50～100個/cm^3,夏期に200～300個/cm^3のときが多かった.しかし,日々の濃度は気象状態によってかなり変動した.特に冬期においてもブリザードの来襲時には1000個/cm^3以上増加することが認められた.3月には日変化が見られるときがあった. Concentration of Aitken particles was measured by means of an improved Pollak type counter for a period of one year from February 1977 to January 1978 at Syowa Station (69.0°s, 39.6゜E), Antaictica Concentration of Aitken particles was lower in the winter season than in the summer season, thus revealing an annual variation. Concentrations of 50 to 100 cm^<-3> were predommant in the winter season and concentrations of 200 to 300 were common in the summer season. However, the concentrations varied largely from day to day due to weather conditions. Especially, concentrations of aerosols increased during a snowstorm (blizzard) even in the winter season and the value exceeded 1000 narticles cm^<-3> departmental bulletin paper